Potensi Kriminalisasi Kritik terhadap Presiden dalam Pasal 218 dan Pasal 219 KUHP Nasional Ditinjau dari Perspektif Hukum Pidana - Fitrichia Milnalita; Ai Permanasari (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The guarantee of freedom of expression in Indonesia, including criticism of the President, confronts Articles 218 and 219 of Law Number 1 of 2023 on the National Criminal Code. The unclear boundary between criticism and insult creates a potential criminalization of constitutionally protected expression. This normative legal research, employing statutory and conceptual approaches, aims to analyze this boundary and to formulate interpretive parameters for preventing such criminalization. The findings show that criticism and insult cannot always be strictly distinguished because the two frequently overlap, so three interpretive parameters are required: the object of the expression, its relevance to the public interest and the proportionality of the criminal sanction. Articles 218 and 219 must therefore be applied carefully and proportionately so that criticism of public policy oriented toward the public interest is not criminalized.